PENGARUH CURRENT RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR TEKSTIL DAN GARMEN DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Agnes Dwi Putri Sihombing; Inggrid prettysia; Aldi Pratama Butar-butar; Herlin Munthe (Mount Hope Economic Global Journal, 2024)
The purpose of the study was to determine the effect of the current ratio on stock prices on the verified manufacturing of the Garment & Textile Sub Sector on the Indonesia Stock Exchange in 2019-2021. The research method is this assessment of quantitative methods and samples used this assessment of 48 samples taken from the number of samples totaling 16 companies multiplied by the 3 -year research period (16x3). The results of the study are the current ratio variable has a positive and insignificant impact on the variable price of the stock manufacturing company of the garment & textile subsector on the IDX since 2019-2021. The results of this study can be said if CR can be used as a basis for consideration in buying shares. As for the limitations of this assessment that must be considered for the next review, this researcher only examines one variable and only tektis and garment companies, other variables need to further observe what aspects come to the stock price.